An Empirical Analysis of the Determinants of Learner Centeredness using Ordinal Logistic Regression - Sukumar K, Sreeja (JOURNAL OF INDIAN EDUCATION, 2022)
As part of quality improvement initiatives of the National Education Policy, the government made radical changes in the instructional style in the classrooms and provided training to the teachers in implementing activity oriented and learner centred curriculum. However, teacher’s apprehension about the effectiveness of Learner Centred Strategies (LCS), the increase in workload due to the vast syllabus, high teacher-student ratio, overall reluctance to change one’s own teaching style; particularly as one acquires more experience and ineffectiveness of the training provided for implementing LCS are all probable issues which influences adoption of learner centred strategies. This study examines the extent to which various learner centred strategies (LCS) have been implemented in schools and identifies the determinants of learner centeredness in classrooms. Ordinal logistic regression is used to predict the dependent variable with ordered multiple categories and other independent variables including type of school, teaching experience, teacher-student ratio, basic entry quality of the students, vast syllabus, training effectiveness and the subject taught by a teacher. Data on the intensity of use of various LCS was collected from 300 teachers using a pre-tested structured interview schedule. The hypotheses were tested using one sample t test. The study found that the use of LCS was slightly above average and that out of the various factors, the subject taught by a teacher and the teacher-student ratio were found to be highly significant in influencing the extent of use of various LCS.